Surface Ammonia-Oxidizer Abundance During the Late Summer in the West Antarctic Coastal System - Alcamán-Arias, María E.; Cifuentes-Anticevic, Jerónimo; Díez, Beatriz; Testa, Giovanni; Troncoso, Macarena; Bello, Estrella; Farías, Laura (Frontiers in Microbiology, 2022)
Marine ammonia oxidizers that oxidize ammonium to nitrite are abundant in polar waters, especially during the winter in the deeper mixed-layer of West Antarctic Peninsula (WAP) waters. However, the activity and abundance of ammonia-oxidizers during the summer in surface coastal Antarctic waters remain unclear. In this study, the ammonia-oxidation rates, abundance and identity of ammonia-oxidizing bacteria (AOB) and archaea (AOA) were evaluated in the marine surface layer (to 30 m depth) in Chile Bay (Greenwich Island, WAP) over three consecutive late-summer periods (2017, 2018 and 2019). Ammonia-oxidation rates of 68.31 nmol N L-1 d-1 (2018) and 37.28 nmol N L-1 d-1 (2019) were detected from illuminated 2 m seawater incubations. However, high ammonia-oxidation rates between 267.75 and 109.38 nmol N L-1 d-1 were obtained under the dark condition at 30 m in 2018 and 2019, respectively. During the late-summer sampling periods both stratifying and mixing events occurring in the water column over short timescales (February-March). Metagenomic analysis of seven nitrogen cycle modules revealed the presence of ammonia-oxidizers, such as the Archaea Nitrosopumilus and the Bacteria Nitrosomonas and Nitrosospira, with AOA often being more abundant than AOB. However, quantification of specific amoA gene transcripts showed number of AOB being two orders of magnitude higher than AOA, with Nitrosomonas representing the most transcriptionally active AOB in the surface waters. Additionally, Candidatus Nitrosopelagicus and Nitrosopumilus, phylogenetically related to surface members of the NP-ε and NP-γ clades respectively, were the predominant AOA. Our findings expand the known distribution of ammonium-oxidizers to the marine surface layer, exposing their potential ecological role in supporting the marine Antarctic system during the productive summer periods.